Feminist and Pessimist Existentialism in Kate Chopin’s “The Story of an Hour”: A Systemic Functional Grammar Analysis - Bima Iqbal Khadafi (Journal of English Language Studies, 2021)
This article interprets Kate Chopin’s “The Story of an Hour” using systemic functional grammar analyses (genre, transitivity, mood structure, and thematic structure) and thus implements the view that textual or linguistic justification is crucial for a credible literary reading. The SFG analyses result in the textual symptoms signifying that the short story deals with existential and feminist issues pessimistically that calls for a reexamination of Sartre’s and Beauvoir’s existentialism –especially on the notion of freedom, intentionality, and desire. However, the implementation of SFG itself raises a problem since the interpretation can be achieved without even implementing it in the first place. This research, therefore, highlights the question of the position that linguistic analysis has in literary reading; re-addressing the fundamental philosophical problem on the notion of credibility, objectivity, and methodology. However, the application of SFG is very useful in understanding Kate Chopin’s literary style and the proof of the non-existing line between language use and gender.